The Role of Anti-EGFR Monoclonal Antibody in mCRC Maintenance Therapy - Yuan, Meiqin; Wang, Zeng; Lv, Wangxia; Pan, Hongming (Frontiers in Molecular Biosciences, 2022)
Background: Epidermal growth factor receptor (EGFR) monoclonal antibodies (mAbs) combined with chemotherapy in patients with RAS (rat sarcoma viral oncogene homolog) wild-type metastatic colorectal cancer (mCRC) can alleviate and stabilize the disease, effectively prolong the progression-free survival (PFS) and overall survival (OS), and improve the overall response rate (ORR), which is the first-line treatment standard scheme for RAS wild-type mCRC currently. However, whether anti-EGFR mAb can be used for the maintenance treatment after the first-line treatment of mCRC remains controversial. We reviewed the recent studies on anti-EGFR mAb. The contents include five parts, introduction, anti-EGFR mAb in mCRC and its status in first-line therapy, establishment of the maintenance treatment pattern after the standard first-line treatment for mCRC, research progress of anti-EGFR mAb in mCRC maintenance therapy, and conclusion. More studies support the maintenance treatment of anti-EGFR mAb, but some researchers raise the problems about high cost and drug resistance. Despite lack of the maintenance evidence of anti-EGFR mAb, especially lack of large-scale phase III prospective clinical trials, with the emergence of new evidence and more accurate screening of treatment-dominant groups, maintenance therapy with anti-EGFR mAb monotherapy or anti-EGFR mAb combined with fluorouracil-based schemes after first-line chemotherapy combined with anti-EGFR mAb therapy might strive for more treatment opportunities, optimize treatment strategies and prolong treatment continuity, and finally, lead to more survival benefit for suitable patients.